The Effect of Palm Oil Prices and Household Consumption Levels on the Welfare of Oil Palm Farmers in Konawe Regency (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
This study aims to analyze the influence of prices and productivity on the welfare of independent oil palm farmers in Andabia Village, Anggaberi District, Konawe Regency. The number of respondents in this study was 24 people taken by census. The analysis method used includes descriptive statistical analysis, with multiple linear regression analysis. Based on the results of the analysis, it shows that the influence of the palm oil price variable on the welfare of oil palm farmers is 0.02 one unit with a calculated t value greater than the t table value (1.924> 1.720) and a significance level smaller than 0.05 (0.02 <0.05) partially has a significant effect on the welfare of oil palm farmers. The influence of the productivity variable on the welfare of oil palm farmers is 0.000 one unit, with a calculated t value greater than the t table value (5.046> 1.663) and a significance level smaller than 0.05 (0.000 <0.05) partially has a significant effect on the welfare of oil palm farmers. The influence of palm oil price and productivity variables simultaneously has a significant influence on the welfare of oil palm farmers. From the F test, the results of the calculation of F count> F table (170,465> 3.07) with a significance level of 0.001 <0.05. This shows that the price and productivity variables together have a significant influence on the welfare of farmers in Andabia Village, Anggaberi District, Konawe Regency.